Implications of Treatment Modality on Chronic Opioid Use Following Treatment for Head and Neck Cancer. (April 2021) - Bollig, Craig A.; Kinealy, Brian P.; Gilley, David R.; Clark, Andrew D.; Galloway, Tabitha L.I.; Zitsch, Robert P.; Jorgensen, Jeffrey B.; Biedermann, Gregory B.
Objective: To investigate the relationship between treatment modality and chronic opioid use in a large cohort of patients with head and neck cancer. Study Design: Retrospective cohort study. Setting: Single academic center. Methods: There were 388 patients with head and neck cancer treated between January 2011 and December 2017 who met inclusion criteria. Clinical risk factors for opioid use at 3 and 6 months were determined with univariate and multivariate analyses. Results: The prevalence of opioid use was 43.0% at 3 months and 33.2% at 6 months. On multivariate analysis, primary chemoradiation (odds ratio [OR], 4.04; 95% CI, 1.91-8.55) and surgery with adjuvant chemoradiation (OR, 2.39; 95% CI, 1.09-5.26) were associated with opioid use at 3 months. Additional risk factors at that time point included pretreatment opioid use (OR, 7.63; 95% CI, 4.09-14.21) and decreasing age (OR, 1.03; 95% CI, 1.01-1.06). At 6 months, primary chemoradiation (OR, 2.40; 95% CI, 1.34-4.28), pretreatment opioid use (OR, 5.86; 95% CI, 3.30-10.38), current tobacco use (OR, 2.00; 95% CI, 1.18-3.40), and psychiatric disorder (OR, 1.79; 95% CI, 1.02-3.14) were associated with opioid use. Conclusion: Of the patients who receive different treatment modalities, those receiving primary chemoradiation are independently at highest risk for chronic opioid use. Other risk factors include pretreatment opioid use, tobacco use, and a psychiatric disorder. In an effort to reduce their risk of chronic opioid use, preventative strategies should be especially directed to these patients.